2017
DOI: 10.1001/jamasurg.2017.0092
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Vascular Exposure and Fasciotomy Among Surgical Residents Before and After Training Compared With Experts

Abstract: This study found that ASSET training improved resident procedural skills for up to 18 months. Performance was highly variable. Interval experience after training affected performance. Pretraining skill identified competency of residents vs experts. Extremity vascular and fasciotomy performance evaluations suggest the need for specific anatomical training interventions in residents with IPS deciles less than 0.5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Fifty‐one studies were included in the review, of which 47 were full‐text original research articles and four were conference posters. The main characteristics of studies, including OCEBM and mean MERSQI scores are shown in Tables S2 – S5 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifty‐one studies were included in the review, of which 47 were full‐text original research articles and four were conference posters. The main characteristics of studies, including OCEBM and mean MERSQI scores are shown in Tables S2 – S5 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Various score‐based methods were also used, including procedure scores, global rating scale (GRS), OSATS (Objective Structured Assessment of Technical Skills in Surgery) and the GOALS (Global Operative Assessment of Laparoscopic Skills) scale. Seven of the 23 studies were RCTs and 16 were cohort studies. Of the seven RCTs, three compared cadaveric simulation with no simulation training, and four compared cadaveric simulation with low‐fidelity simulation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations